2015
DOI: 10.1007/s00774-015-0671-5
|View full text |Cite
|
Sign up to set email alerts
|

Circulating sclerostin and dickkopf-1 levels in ossification of the posterior longitudinal ligament of the spine

Abstract: Sclerostin and dickkopf-1(DKK1) are Wnt/β-catenin signal antagonists that play an important role in bone formation. Ossification of the posterior longitudinal ligament (OPLL) of the spine is characterized by pathological ectopic ossification of the posterior longitudinal ligament and ankylosing spinal hyperostosis. The aims of this study were to evaluate serum sclerostin and DKK1 levels in persons with OPLL and to identify its relationship with bone metabolism and bone mass in persons with OPLL. This was a cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 37 publications
2
31
2
Order By: Relevance
“…3 ). Consistent with the model of Kashii et al [ 37 ], we suggest that the higher serum SOST levels are counterbalanced by underproduction of DKK1. Fifty percent of the patients with DISH also have OPLL, and OPLL is thought to be a subtype of DISH [ 38 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…3 ). Consistent with the model of Kashii et al [ 37 ], we suggest that the higher serum SOST levels are counterbalanced by underproduction of DKK1. Fifty percent of the patients with DISH also have OPLL, and OPLL is thought to be a subtype of DISH [ 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…SOST plays a critical role in bone and mineral metabolism. Kashii et al [ 37 ] showed that systemic secretion of SOST increases with higher bone mass in men with OPLL and that serum SOST levels negatively correlate with DKK1 levels in men with OPLL. Higher serum SOST levels are counterbalanced by underproduction of DKK1 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum sclerostin and DKK1 levels are negatively correlated in male OPLL subjects. Systemic secretion of sclerostin also increases with advancing age and with higher bone mass in male OPLL subjects [ 84 ].…”
Section: Opll Biomarkersmentioning
confidence: 99%
“…At present, several genetic and non-genetic factors are involved in the pathological progress of OPLL. Aberrant levels of broblast growth factor-23 [3], leptin [4], dickkopf-1 and sclerostin [5], as well as mechanical stress signaling have been identi ed as main contributing factors in the development of OPLL [6][7][8].…”
Section: Introductionmentioning
confidence: 99%